Perception of pain and influences on opioid use in implant‐based breast reconstruction patients. Issue 9 (4th June 2020) - Egan, Katie G.; De Souza, Michelle; Allen, Andrea L.; Muenks, Elizabeth; Nazir, Niaman; Korentager, Richard
Abstract: Although there has been a recent focus on decreasing opioid prescribing through alternative pain medication protocols, the patient's perception of pain related to breast reconstructive surgeries has not been well described. We sought to evaluate patient perception of pain control as it influences opioid use. We hypothesize that modifiable factors may influence patterns in pain perception and postoperative opioid use. Patients undergoing consultation for mastectomy with immediate, implant‐based breast reconstruction were enrolled in a prospective, cohort survey study. A survey was administered at preoperative and postoperative appointments to collect data on pain expectations and pain control. Of 100 patients enrolled, 85% completed the postoperative survey. Over half of patients (52%) reported feeling anxious about pain control after surgery. Patients with preoperative opioid use were more likely to expect complete relief of pain postoperatively ( P  = .038). Patients with psychiatric comorbidity were more likely to report feeling anxious about postoperative pain ( P  = .012; 70% vs 42%; OR 3.0 CI 1.2‐7.4). Patients who reported feeling anxious about pain control preoperatively were more likely to report trying opioids ( P  = .047; 67% vs 44%; OR 2.5 CI 1.0‐6.1) and benzodiazepines ( P  = .020; 80% vs 56%; OR 3.0 CI 1.2‐8.0) postoperatively. Anxiety related to pain control is common and results in an increased likelihood of trying opioid and benzodiazepine medications postoperatively. This presents an opportunity to educate patients preoperatively by addressing anxiety related to pain control to decrease controlled substance use.